The Sacred and Profane in English Renaissance Literature - Papazian, Mary Arshagouni (University of Delaware Press, 2008)
"This collection of thirteen original essays focuses squarely on the question of how properly to define the intersection between the sacred and profane in early modern English literature. Growing out of the work of church historians of the previous decade, and the renewed interest in our own time in questions of how the religious and secular realms overlap and (re)define each other, the contributors to this volume focus their attention on defining anew the tension between the sacred and profane in this period. Fundamental to this reframing is a strong belief among all contributors that the sacred and profane must be defined in relation to each other. Thus, the essays in this volume seek to advance more nuanced approaches to these issues that enable us to move beyond simplistic categories whereby the sacred and profane - and sacred and profane literature - occupied several different spheres, were produced by different writers, and spoke to different audiences."--Jacket.
Keywords: 16th century; 16th century; Holy, The, in literature; Secularism in literature; Sacred space in literature; Civilization, Secular; Renaissance; 17th century; Great Britain; 17th century; Religion and literature; Early modern, 1500-1700; England; Christian literature, English; English literature; Great Britain; History; History and criticism; Devotional literature, English; History and criticism; Great Britain; History and criticism; Religion and literature; Intellectual life; dept.pres; faculty_collection; unidentified